THE ANALYSIS OF RESULTS PRINCIPAL SUPERVISION ANDACHIEVEMENT MOTIVATION FOR TEACHER PERFORMANCEIN SMA SATYA DHARMA BALUNG - Arief Rahmat Hidayat; Gatot Sugeng Purwono; Hary Sulaksono (MBA - Journal of Management and Business Aplication, 2019)
The purpose of this research is to analyze and test the effect of principal supervision and teacher achievement motivation on teacher performance in SMA Satya Dharma Balung, either simultaneously or partially. This research includes explanatory research survey. The location of this research is at SMA Satya Dharma Balung. The independent variable of this research were the principal supervision and teacher achievement motivation (X) while the dependent variable of this research was the teacher performance (Y). The subject of this research was all of the teachers at SMA Satya Dharma Balung which also became the sample. Data collection methods used in this study were observation, direct interview, questionnaire, and documentation. While the data analysis used was multiple linear regression. Based on the results of the research noted that the influence of the principal supervision and teacher achievement motivation had a significant effect on the teacher performance at SMA Satya Dharma Balung either partially or simultaneously. Partial test result proved by t -count value: 1). The t -count value of the principal's supervision variable is 2.054 with the probability value of 0.048, while the t - table value was 2.035. Therefore t-count > t-table (2.054 > 2.035). 2). The value of t-count of the teacher achievement motivation is 3.863 with the probability value 0.000, while t-table value was 2.035, so t-count > t-table (3,863 > 2,035). The effective contribution of principal supervision and teacher achievement motivation toward teacher performance at SMA Satya Dharma Balung was 71,4% of teacher achievement motivation variable as the most dominant variable (47,8%). The final result of this research was to improve the performance of the achievement which could also improve the teacher's performance and commitment.